Always [large type] : a novel - Jio, Sarah (Center Point Pub, 2017)
"Set amidst the Seattle music scene of the 90s as well as the present day, Always parallels the past and present in a unique love story about a woman who discovers what she's willing to save and what she will sacrifice"--